2013
DOI: 10.1039/c3dt00055a
|View full text |Cite
|
Sign up to set email alerts
|

A microporous luminescent europium metal–organic framework for nitro explosive sensing

Abstract: A microporous metal–organic framework (MOF) Eu3(MFDA)4(NO3)(DMF)3 (1, H2MFDA = 9,9-dimethylfluorene-2,7-dicarboxylic acid) has been solvothermally synthesized and structurally characterized by single-crystal X-ray diffraction. 1 is a three-dimensional coordination polymer with pcu type rod-packing structure, through which 1D rhombic channels penetrate. The solvent-free form 1a could be obtained by direct heating of 1. Both 1 and 1a exhibit high intensity red light emissions with high quantum yields and long lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(96 citation statements)
references
References 34 publications
(6 reference statements)
8
87
0
1
Order By: Relevance
“…Given the above concerns, we prepared a semi-rigid ligand with four carboxylate groups as coordination sites and two amide groups as functional sites, namely bis (3,5-dicarboxypheny1) 3 (MOF1). As we expected, the introduction of aromatic base ligands with amide groups into MOF1 provided a promising way to construct new porous materials for selectively sensing aromatic amines as well as photocatalytic degradation of organic dyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the above concerns, we prepared a semi-rigid ligand with four carboxylate groups as coordination sites and two amide groups as functional sites, namely bis (3,5-dicarboxypheny1) 3 (MOF1). As we expected, the introduction of aromatic base ligands with amide groups into MOF1 provided a promising way to construct new porous materials for selectively sensing aromatic amines as well as photocatalytic degradation of organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Recently, increased efforts have been focused on the synthesis of luminescent porous metal-organic frameworks for detecting nitro-aromatic explosives due to the importance of nitro compounds in homeland security and environmental safety. [2][3][4][5][6][7][8][9][10][11] Most of the reported MOF-based sensing materials are constructed with aromatic ligands because the π electron systems of the ligands endow the MOFs with photoluminescence properties and provide potential supramolecular recognition sites for hydrogen bonds, π-π stack-1 its strong fluorescence emission and microporous structure. In addition, the visible-light-driven photocatalytic degradation of Rhodamine B (RhB) by MOF1 and polyaniline (PANI) composite material (named PANI/MOF1), which was prepared by loading PANI onto the surface of MOF1, was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several examples for sensing a variety of species (i.e. gases, metal ions and organic molecules) have been reported [326,[365][366][367]. As an example, ion sensing of Fe 3+ and Zn +2 has been achieved utilizing Eu-BTPCA MOFs (BTPCA 3− = 1,1′,1″-(benzene-1,3,5-triyl)tripiperidine-4-carboxylate) [326].…”
Section: +mentioning
confidence: 99%
“…Organic molecules which are good electron donors or acceptors can also influence the ET efficiency and thus the intensity of lanthanide luminescence. Based on that, 10 different nitroaromatic compounds have been detected by measuring the luminescence quenching percentage of Eu-MOFs [Eu 3 (MFDA) 4 (NO 3 )(DMF) 3 ], (H 2 MFDA = 9,9-imethylfluorene-2,7-dicarboxylic acid) [365].…”
Section: +mentioning
confidence: 99%
“…Pioneering work within this field was performed by Li et al who demonstrated the sensitive detection of DMNB and 2,4-DNT in the vapour phase. 37 This work inspired a number of other researchers who subsequently demonstrated the successful detection of explosives, with some selectivity, using zinc, [38][39][40][41][42][43] cadmium, [44][45][46] lithium, 47 indium, 48 europium, [49][50][51][52] and terbium containing metal-organic frameworks. 53 However, the majority of the published research reports the detection of explosives using MOFs through solution-based titrations.…”
Section: −3mentioning
confidence: 99%